Studies on Indole Derivatives. XV. Synthesis of Indoxyl Derivatives. (1). Crystal and Molecular Structure of Anhydro-2-benzyl-1-mercapto-3-methyl-9-oxo-(9H)-imidazo[1, 5-α]indolium Hydroxide - HATA, TADASHI; SATO, SADAO; MATSUDA, YOSHIRO; TOMINAGA, YOSHINORI; KOBAYASHI, GORO; TAMURA, CHIHIRO; NATSUKI, REIKO (Chemical & pharmaceutical bulletin, 1973)
The new mesoionic compounds, anhydro-2-benzyl-1-mercapto-3-methyl-9-oxo-(9H)-imidazo[1, 5-a]indolium hydroxide, was synthesized by the reaction of 1-acetyl-3-indolinone, carbon disulfide, and benzylamine. The structure has been determined by an X-ray analysis. The Crystals are monoclinic, a=11.58, b=8.52, c=15.50 Å, β=102.7°, and the space group is P21/C. The intensities of all independent reflections were measured with a Rigaku auto differactometer and a total of 887 were collected and employed for structure determination by the heavy atom method. The final R factor is down to 0.067 by a block diagnal least-squares refinement. The mesoionic imidazolium ring system is almost planar. The C-S bond of 1.678 Å agrees well with the accepted value of 1.78 Å, methyl group of 1.449 Å attached with an imidazolium ring indicates some double bond character.